Beliefs and The Religious Syncretism of people in the Thonburi period, 1767 - 1782 - Sompongjaroen, Wirawan (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
This research aims to 1) Studying the historical background of the Thonburi period, 1767 – 1782. 2) Studying the beliefs of people in the Thonburi period, 1767 - 1782. 3) Studying of the integration of beliefs in the Thonburi period, 1767 – 1782. The study method is Using of historical research methods Content analysis study design and primary documents. The study results found that The historical background of the Thonburi period has four influences on the beliefs of the people is a belief in local ghosts, Brahmin-Hindu, Buddhism and Women's Household. There are two issues regarding the integration of beliefs in King Taksin and Thonburi City Plan.